A Baranya-háromszög területi-közigazgatási integrálásának kérdései Jugoszláviában : 1918-1945 - Hajdú, Zoltán (Közép-Európai Közlemények, 2011)
The end of the First World War resulted very complicated territorial structures around the new state borders of the new Hungary. The paper is analysing the situation of Baranya-triangle, on the common borders of Hungary and the new Yugoslavia. A relatively little (1100 km2) area with not so huge number of population (50 thousand) turned to be a key problem in the new Yugoslavia among Croats and Serbs. Between 1918–1941 the area belonged to Voivodina, between 1941–1944 to Hungary, and after 1945 to Croatia int he framework of federal Yugoslavia.